2016
DOI: 10.1007/s00415-016-8125-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative MRI for deep brain stimulation lead placement in Parkinson’s disease: 1 year motor and neuropsychological outcomes

Abstract: Traditional deep brain stimulation requires intraoperative neurophysiological confirmation of electrode placement. Recently, purely image guided methods are being evaluated as to their clinical efficacy in comparison to surgery using microelectrode recordings. We used the ClearPoint(®) system to place electrodes in both the subthalamic nucleus and globus pallidus internus in patients with advanced Parkinson's disease. Off medication UPDRS scores were assessed before and 1 year after surgery as well as pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The mean radial error for asleep DBS in our series was less than 1 mm for both targets (GPi 0.8 ± 0.4 mm, STN 0.9 ± 0.3 mm), which is in line with that in previous reports of MRI-and CT-guided asleep DBS techniques (0.6-1.2 mm). 3,18,23,28 The incidence of specific adverse events did not differ significantly between awake and asleep cohorts. Balance and speech disturbances were the most commonly reported symptoms at 6-month follow-up across all groups, and incidences were in line with those previously published for awake and asleep DBS series.…”
Section: Secondary Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…The mean radial error for asleep DBS in our series was less than 1 mm for both targets (GPi 0.8 ± 0.4 mm, STN 0.9 ± 0.3 mm), which is in line with that in previous reports of MRI-and CT-guided asleep DBS techniques (0.6-1.2 mm). 3,18,23,28 The incidence of specific adverse events did not differ significantly between awake and asleep cohorts. Balance and speech disturbances were the most commonly reported symptoms at 6-month follow-up across all groups, and incidences were in line with those previously published for awake and asleep DBS series.…”
Section: Secondary Outcomesmentioning
confidence: 91%
“…3,5,13,15,34,35 Although level 1 evidence has demonstrated that the awake DBS method for PD results in significant improvement in functional outcomes of patients, 8,19,20,21,25,32 a persistent criticism of the asleep DBS technique is that the procedure relies on the assumption that accurately placing a DBS lead at an anatomical target defined on MRI will correlate with improved outcomes. 15 Several initial series of PD patients undergoing asleep DBS have demonstrated motor and quality-of-life outcomes comparable to those in historical studies using neurophysiological testing, 9,16,22,28,29 but few reports have made direct comparisons between asleep DBS patients and control patients undergoing traditional awake surgery. 18,26 To address this gap, we report clinical outcomes for patients undergoing bilateral subthalamic nucleus (STN) or globus pallidus internus (GPi) stimulation using either awake or asleep DBS at a single institution.…”
mentioning
confidence: 97%
“…The key features of this platform are 1) patient positioning on the MRI gantry under general anesthesia; 2) definition of target coordinates with respect to the MRI isocenter rather than to a separate stereotactic space; 3) trajectory alignment and cannula insertion via a burr hole-mounted trajectory guide in place of a traditional stereotactic frame-based system; 4) integration of planning, insertion, and real-time MRI confirmation of cannula placement and subsequent infusate distribution during a single procedure; 5) cannula design involving a small inner lumen to allow for low priming volume and minimal waste of therapeutic agents, and a two-step tip that minimizes drug reflux. The accuracy of the ClearPoint system was first validated preclinically in nonhuman primate infusion studies [25], and subsequently has been validated extensively for the clinical placement of deep brain stimulation leads, with average targeting errors on the order of 1 mm [28][29][30][31]. This platform enables cannula placement to be aligned precisely with the planned trajectory, optimizing the ability to use the two-step design for controlling the start of the infusion within the target structure ( Fig.…”
Section: Surgical Platformmentioning
confidence: 99%
“…For example, target confirmation through fusion with an iCT scan in asleep DBS surgery appears to shorten the duration of surgery . While there are few published research studies using intraoperative MRI , one reported advantage is that the intraoperative (or interventional) MRI (iMRI) approach uses near real‐time acquisition of images to prospectively guide both trajectory planning and the intended targets verification before electrode placement . Therefore, interventional MRI is most useful for DBS targets that are visible on standard clinical imaging and provides a method for objective verification of intended targets .…”
Section: Surgical Techniquementioning
confidence: 99%
“…Other studies demonstrated that the interventional MRI‐based approaches could achieve submillimetric accuracy, with mean errors near 0.7 mm and standard deviations near 0.3 mm . For example, Sidiropoulos et al used the ClearPoint system to place electrodes in both the STN and GPi in patients with advanced PD . They found that the mean radial error for the STN group was 1.2 ± 0.7 mm and for the GPi group 0.8 ± 0.3 mm 47 .…”
Section: Surgical Techniquementioning
confidence: 99%